Evaluación de la Planta de Tratamiento de Aguas Residuales de la Urbanización Blanquillo, cantón de Oreamuno - Rodríguez-Fonseca, Hellen Karina (Instituto Tecnológico de Costa Rica, 2012)
The district of San Rafael of Oreamuno includes 7.429 houses according to preliminary data of the INEC corresponding to 2011. Whereas, by 2007 according to a study of PRUGAM, the canton of Oreamuno did not count with a single home that employed the connection to a sanitary sewer system has the mean to collect wastewaters. However, there are registries that indicate that to the date, the Municipality of Oreamuno is in charge of two wastewater treatment plants, the Vista Hermosa plant and the Blanquillo plant. The wastewater treatment plant of the Urbanization Blanquillo was created in 1994 and according to the records of the Municipality of Oreamuno, it is not until 2011 when the municipal authorities show interest to make the necessary works to undertake the proper function of the plant are initiated. This study proposed to assess and evaluate the improvements to effectuate to the actual wastewater treatment plant of the Urbanization Blanquillo, in Oreamuno. The optimization and/or improvement measures suggested were determined regarding the performance evaluation of the wastewater treatment plant under the actual operating conditions. Such conditions reflected through a physical-chemical outline of the inlet and outlet wastewaters and a valuation of the infrastructure of the plant. In addition, the generating body was characterized; sample of the population of the urbanization. Before proceeding with the evaluation of the plant, it was necessary to clean all the components of the treatment system, thereby delaying the launch process of the wastewater treatment plant. Process that allowed to acknowledged the need make improvements to the following components: amplify the screen component, replace the inner pipe in the settling tank, increase the level of the filtering material in the UASB, change and install valves for the extraction of sludge and finish roofing the uncover portion of the sludge bed, with an estimated cost of ¢5.189.739,91, including the construction of a guardhouse and purchase of equipment.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica. Escuela de Química, 2012.
Keywords: Municipalidad de Oreamuno; Urbanización Blanquillo; Tratamiento anaeróbico; Planta de tratamiento; Aguas residuales